Ultrafast lasers and their applications - Sotor, Jaroslaw; Soboń, Grzegorz (Photonics Letters of Poland, 2016)
The editors introduce the special issue on "Ultrafast lasers and their applications". It covers topics from ultrashort laser pulses generation using nanomaterials-based saturable absorbers to practical applications of such lasers in spectroscopy, supercontinuum generation and laser micromachining. The issue contains nine papers tightly focused on the main topic and two regular papers.